2007
DOI: 10.1002/jpln.200625238
|View full text |Cite
|
Sign up to set email alerts
|

Mercury accumulation and resistance to mercury stress in Rumex induratus and Marrubium vulgare grown in perlite

Abstract: SummaryPlants of Rumex induratus and Marrubium vulgare, collected in the mining area of Almadén, were transferred to pots and grown for 2 months using perlite as substrate and treated with soluble mercury (Hg) in the applied nutrient solution. Mercury resistance, Hg bioaccumulation, and some stress biomarkers were investigated in both plant species. Mercury concentration increased in both plant species in response to Hg supply, but R. induratus was more effective in Hg accumulation. Rumex induratus and M. vulg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 34 publications
3
20
2
Order By: Relevance
“…The supply of Hg both at moderate and high concentration reduced the concentrations of K, Ca and Mg. Reduction of K, Ca and other mineral nutrients under the influence of Hg have been reported in M. Vulgare, R. induratus (Moreno-Jimenz et al 2007) and V. spiralis (Gupta and Chandra 1998). Increased electrolytic leakage in the root tissues of Hg treated plants as observed in our study might have reduced the uptake of nutrients from the growth medium.…”
Section: Discussionsupporting
confidence: 78%
“…The supply of Hg both at moderate and high concentration reduced the concentrations of K, Ca and Mg. Reduction of K, Ca and other mineral nutrients under the influence of Hg have been reported in M. Vulgare, R. induratus (Moreno-Jimenz et al 2007) and V. spiralis (Gupta and Chandra 1998). Increased electrolytic leakage in the root tissues of Hg treated plants as observed in our study might have reduced the uptake of nutrients from the growth medium.…”
Section: Discussionsupporting
confidence: 78%
“…A significant decrease in Cu, Zn, Fe and Mn concentrations in P. glomerata plants exposed to Hg was observed, but most Zn, Mn, and Cu in the roots (Table 2). In contrast to our data, MORENO-JIMENEZ et al (2007) reported that Hg increased the concentration of Fe by more than 40% in roots of Marrubium vulgare. Interestingly, RODRÍGUES et al (2009) reported that the concentration of Fe in roots increased in plants exposed to Hg at 50µM and decreased in roots of plants exposed to Hg at 100µM.…”
Section: Resultscontrasting
confidence: 99%
“…It has been reported that in plants, Hg can replace some nutrients, such as Mg, Zn, and Mn, causing a reduction in chlorophyll production and inhibiting the photosynthetic electron transport chain (RUIZ et al, 2003;PATRA et al, 2004). MORENO-JIMENEZ et al (2007) reported that Hg increased the concentration of Fe by more than 40% in roots of Marrubium vulgare, but the translocation of Fe was reduced.…”
Section: Introductionmentioning
confidence: 99%
“…A strong correlation between S concentration in plant tissue and biomass increase has been found by other authors [43]. Further, it has been shown that biomass increase can be induced by non-toxic concentrations of Hg [44] and other heavy metals, e.g., Pb [45].…”
Section: Speciesmentioning
confidence: 86%